Revisiting Research on Grammatical Gender Acquisition by Russian-Speaking Children with Developmental Language Disorder - Ogneva, Anastasiia (East European Journal of Psycholinguistics, 2019)
Although both Developmental Language Disorder (DLD) and grammatical gender acquisition have been the focus of scientific interest for decades, a few research has been conducted in order to explore how DLD Russian-speaking children acquire this linguistic category. One of the main reasons for this is the difficulty of recruiting DLD children as we still cannot reliably identify these children. Previous studies claim that typically developing children acquire grammatical gender at about 3-4 years of age, but have difficulties with neuter gender up to 6 years of age. This brief report aims at providing the theoretical background of a research in process. The review deals with the issue of grammatical gender acquisition by Russian-speaking children diagnosed with DLD. Specifically, this paper reviews i) the main findings of studies on gender acquisition in typically developing Russian-speaking children, ii) the outcomes of research on how Russian-speaking DLD children make use of grammatical gender.ReferencesAnderson, R.T. & Souto, S.M. (2005). The use of articles by monolingual Puerto Rican Spanish-speaking children with specific language impairment. Applied Psycholinguistics, 26(4), 621-647.Bedore, L. M., & Leonard, L. B. (2001). Grammatical morphology deficits in Spanish-speaking children with specific language impairment. Journal of Speech, Language, and Hearing Research, 44(4), 905–924Bishop, D.V.M., Snowling M.J., Thompson, P. A., Greenhalgh Y., & The CATALISE Consortium. (2017): Phase 2 of CATALISE: a multinational and multidisciplinary Delphi consensus study of problems with language development: Terminology. PLoS ONE, 11(7), 1-26.Clahsen, H., Bartke, S. & Göllner S. (1997). Formal features in impaired grammars: A Comparison of English and German SLI children. Journal of Neurolinguistics, 10(2/3), 151-171.Corbett, G. G. (1991). Gender. Cambridge: Cambridge University Press.Гвоздев, А.Н. (1961). Формирование у ребенка грамматического строя русского языка. Москва: АПН РСФСР.Jackson-Maldonado, D. & Maldonado, R. (2017). Grammaticality differences between Spanish-speaking children with specific language impairment and their typically developing peers. International Journal of Language and Communication Disorders, 52(6), 750-765.Leonard, Laurence B. (2014). Children with Specific Language Impairment. Cambridge: The MIT Press.Mitrofanova, N., Rodina, Y., Urek, O. & Westergaard, M. (2018). Bilinguals’ Sensitivity to Grammatical Gender Cues in Russian: The Role of Cumulative Input, Proficiency, and Dominance. Frontiers in Psychology. https://doi.org/10.3389/fpsyg.2018.01894Orgassa, A., & Weerman, F. (2008). Dutch gender in specific language impairment and second language acquisition. Second Language Research, 24(3), 333–364.Popova, M. I. (1973). Grammatical elements of language in the speech of pre-preschool children. In Studies of child language development, (pp. 269–80). C. A. Ferguson & D. I. Slobin (eds). New York: Holt, Rinehart and Winston.Rakhlin, N., Kornilov, S., & Grigorenko, E. (2014). Gender and agreement processing in children with Developmental Language Disorder. Journal of Child Language, 41(2), 241–274.Rodina, Y. (2008). Semantics and morphology: The acquisition of grammatical gender in Russian. Doctoral thesis. Tromso: University of Tromso. Retrieved from: https://munin.uit.no/handle/ 10037/2247.Rodina, Y. & Westeergard M. (2012). A cue-based approach to the acquisition of grammatical gender in Russian. Journal of Child Language, 39(5), 1077-1106.Roulet-Amiot, L., & Jacubowicz, C. (2006). Production and perception of gender agreement in French SLI. Advances in Speech Language Pathology, 8(4), 335–346.Silveira, M. (2006). A preliminary investigation of grammatical gender abilities in Portuguese speaking children with Specific Language Impairment. Unpublished working paper, University College London, Department of Phonetics and Linguistics. Retrieved from: http://www.ucl.ac.uk/ psychlangsci/research/linguistics/publications/wpl/06papers/silveiraTribushinina, E., & Dubinkina, E. (2012). Adjective production by Russian-speaking children with specific language impairment. Clinical Linguistics and Phonetics, 26(6), 554–571.Tribushinina, E., Mak, M., Dubinkina, E. & Mak, W.M. (2018). Adjective production by Russian-speaking children with developmental language disorder and Dutch-Russian simultaneous bilinguals. Applied Psycholinguistics, 39(5), 1033-1064.Цейтлин, С. Н. (2005). Категория рода в детской речи. Проблемы функциональной грамматики: полевые структуры. А.В. Бондаренко (ред.). Санкт-Петербург: Наука, 346-375.Цейтлин, С.Н. (2009). Очерки по словообразованию и формообразованию в детской речи. Москва: Знак.Varlokosta, S. & Nerantzini, M. (2013). Grammatical gender in Specific Language Impairment: Evidence from Determiner-Noun Contexts in Greek. Psychology, 20(3), 338-357.References (translated and transliterated)Anderson, R.T. & Souto, S.M. (2005). The use of articles by monolingual Puerto Rican Spanish-speaking children with specific language impairment. Applied Psycholinguistics, 26(4), 621-647.Bedore, L. M., & Leonard, L. B. (2001). Grammatical morphology deficits in Spanish-speaking children with specific language impairment. Journal of Speech, Language, and Hearing Research, 44(4), 905–924Bishop, D.V.M., Snowling M.J., Thompson, P. A., Greenhalgh Y., & The CATALISE Consortium. (2017): Phase 2 of CATALISE: a multinational and multidisciplinary Delphi consensus study of problems with language development: Terminology. PLoS ONE, 11(7), 1-26.Clahsen, H., Bartke, S. & Göllner S. (1997). Formal features in impaired grammars: A Comparison of English and German SLI children. Journal of Neurolinguistics, 10(2/3), 151-171.Corbett, G. G. (1991). Gender. Cambridge: Cambridge University Press.Гвоздев, А.Н. (1961). Формирование у ребенка грамматического строя русского языка. Москва: АПН РСФСР.Gvozdev, A. N. (1961). Formirovanie u Rebenka Grammatičeskogo Stroja Russkogo Jazyka [The Construction of the Grammatical Basis of the Russian Language in a Child]. Moscow: The Russian Academy of Pedagogical Sciences.Jackson-Maldonado, D. & Maldonado, R. (2017). Grammaticality differences between Spanish-speaking children with specific language impairment and their typically developing peers. International Journal of Language and Communication Disorders, 52(6), 750-765.Leonard, Laurence B. (2014). Children with Specific Language Impairment. Cambridge: The MIT Press.Mitrofanova, N., Rodina, Y., Urek, O. & Westergaard, M. (2018). Bilinguals’ Sensitivity to Grammatical Gender Cues in Russian: The Role of Cumulative Input, Proficiency, and Dominance. Frontiers in Psychology. https://doi.org/10.3389/fpsyg.2018.01894Orgassa, A., & Weerman, F. (2008). Dutch gender in specific language impairment and second language acquisition. Second Language Research, 24(3), 333–364.Popova, M. I. (1973). Grammatical elements of language in the speech of pre-preschool children. In Studies of child language development, (pp. 269–80). C. A. Ferguson & D. I. Slobin (eds). New York: Holt, Rinehart and Winston.Rakhlin, N., Kornilov, S., & Grigorenko, E. (2014). Gender and agreement processing in children with Developmental Language Disorder. Journal of Child Language, 41(2), 241–274.Rodina, Y. (2008). Semantics and morphology: The acquisition of grammatical gender in Russian. Doctoral thesis. Tromso: University of Tromso. Retrieved from: https://munin.uit.no/handle/ 10037/2247.Rodina, Y. & Westeergard M. (2012). A cue-based approach to the acquisition of grammatical gender in Russian. Journal of Child Language, 39(5), 1077-1106.Roulet-Amiot, L., & Jacubowicz, C. (2006). Production and perception of gender agreement in French SLI. Advances in Speech Language Pathology, 8(4), 335–346.Silveira, M. (2006). A preliminary investigation of grammatical gender abilities in Portuguese speaking children with Specific Language Impairment. Unpublished working paper, University College London, Department of Phonetics and Linguistics. Retrieved from: http://www.ucl.ac.uk/ psychlangsci/research/linguistics/publications/wpl/06papers/silveiraTribushinina, E., & Dubinkina, E. (2012). Adjective production by Russian-speaking children with specific language impairment. Clinical Linguistics and Phonetics, 26(6), 554–571.Tribushinina, E., Mak, M., Dubinkina, E. & Mak, W.M. (2018). Adjective production by Russian-speaking children with developmental language disorder and Dutch-Russian simultaneous bilinguals. Applied Psycholinguistics, 39(5), 1033-1064.Цейтлин, С. Н. (2005). Категория рода в детской речи. Проблемы функциональной грамматики: полевые структуры. А.В. Бондаренко (ред.). Санкт-Петербург: Наука, 346-375.Ceitlin, S. N. (2005). Kategorija roda v detskoj reči [The category of gender in child speech]. In Problemy funkcional'noj grammatiki: Polevye struktury [Issues in functional grammar: Field structures], (pp. 346–375). A. V. Bondarko (ed.). S.-Petersburg: Nauka.Цейтлин, С.Н. (2009). Очерки по словообразованию и формообразованию в детской речи. Москва: Знак.Ceitlin, S. N. (2009). Ocherki po slovoobrazovaniju i formoobrazovaniju v detskoj rechi [On Inflection and Derivation in Child Language]. Moscow: Znak.Varlokosta, S. & Nerantzini, M. (2013). Grammatical gender in Specific Language Impairment: Evidence from Determiner-Noun Contexts in Greek. Psychology, 20(3), 338-357.